Taxonomy and IUCN categories of two endemic Scrophularia L Scrophulariaceae species cited in the Data Deficient DD Category - Uzunhi̇sarcikli, Mehmet; Doğan Güner, Ebru; Bi̇lgi̇li̇, Bilgehan (Aperta, 2014)
Scrophularia is represented with 59 species in the Flora of Turkey. This study presents the taxonomy and threatened categories of two endemic Scrophularia L. (Scrophulariaceae) species: S. erzincanica R. Mill and S. capillaris Boiss. & Bal. These species were previously placed in the Data Deficient (DD) category according to Red Data Book of Turkish Plants. This study provides the re-descriptions of taxa and suggests new IUCN categories according to IUCN 2010 threatened categories. Descriptions, localities, distribution map and images of the species are also given.
Keywords: Engineering; Mühendislik; 15. Life on land